Complete the comparison: 3 + 7 > ? A. 7 + 3 B. 10 − 2 C. 9 + 4 D. 8 + 2

Answers

Answer 1
Answer:

According to the information the complete comparison would be: 3 + 7 > 7 + 3

What is the complete comparison?

The comparison "3 + 7 > 7 + 3" is true. Both sides of the inequality are equal to 10, but the left side of the inequality is "3 + 7" and the right side is "7 + 3".

According to the above, we can conclude that since addition is commutative, the order of the numbers doesn't matter, and both sides are equal. Therefore, the comparison is true and complete.

So, we can conclude that the correct and complete comparison would be:

  • 3 + 7 > 7 + 3

Learn more about inequalities in: brainly.com/question/28823603

#SPJ6

Answer 2
Answer: The answer is B

3+7=10

7+3=10
10-2=8
9+4=13
8+2=10

As 10>8
Therefore 7+3>10-2

Related Questions

What is the reference angle for 7pi/2
Can 24 7ths be equal to another fraction or be simplified in another way
Reduce to lowest term18/24
Which of the following is the number of sides for a regular polygon that will not form a regular tessellation?A. 6 B. 4 C. 3 D. 8
Use the two patterns belowadd 5: 5,10,15 ADD 3: 3.6.9 What are the first four ordered pairs formed from corresponding terms of the two patterns? Please Help!! really important

Which choice is the appropriate simplified form and restriction for the variable? 3x^2+9x over x^2-2x-15

Answers

If you would like to know what is the appropriate simplified form and restriction for the variable, you can calculate this using the following steps:

(3x^2 + 9x) / ( x^2 - 2x - 15) = (3x * (x + 3)) / ((x - 5) * (x + 3)) = 3x / (x - 5)

The simplified form is 3x / (x - 5) and the restriction for the variable would be x  5 and x ≠ -3.
(3x^2 + 9x) / ( x^2 -2x -15)

Factor both polynomials

(3x)(x+3) / (x-5)(x+3) = 3x/(x+5)

The simplified form is 3x/(x+5)

The restriction for the variable is x ≠ -3 (this is because you can only simplify the factor x-3 if its value is not zero).

Solve for x: |x − 2| + 10 = 12 x = 0 and x = 4
 x = −4 and x = 0
 x = −20 and x = 4
 No solution

Answers

Let's solve this equation step-by-step!
is the question you've asked us today:
|x − 2| + 10 = 12

Add -10 to both sides:
|x−2|+10+−10=12+10

Solve Absolute Value:
|x−2|=2

✯We know either: 
x−2=2 or x−2=2

(Possibility 1) x−2=2

(Add 2 to both sides) x−2+2=2+2

x=4

(Possibility 2) x−2=−2

(Add 2 to both sides) x−2+2=−2+2

x=0

✯So since we have gotten x=4 and x=0 you answer shall be:

B. x=4 and x=0

✯I hope this helps!

first you can add -10 on both sides so you gonna have :
 l x - 2 l = 12 - 10 ⇒ l x - 2 l = 2 now because of the absolute value you should say : 
1) x - 2 = 2 ⇒ x = 2 + 2 ⇒ x = 4 

2) x- 2 = -2 ⇒ x = -2 +2 ⇒ x = 0 
so the answer is first one :)))
i hope this is helpful 
have a nice day 

Five times a number is less than -45.
inequality:__________?
Solution:__________?

Answers

Answer: 5 times x<-45 the solution is x<-9

Step-by-step explanation:

less than is < and greater than is >

5 x n - 45 is the inequality

Sal's Sandwich Shop sells wraps and sandwiches as part of its lunch specials. The profit on every sandwich is $2 and the profit on every wrap is $3. Sal made a profit of $1,470 from lunch specials last month. The equation 2x + 3y = 1,470 represents Sal's profits last month, where x is the number of sandwich lunch specials sold and y is the number of wrap lunch specials sold.

Answers

If you want to find how the graphs of the functions for the two months are similar and how they are different, here is the answer:

Both are straight lines. 
Both slopes are the same. 
The x and y intercepts are different.

Hope that helps :)

Answer: y = -2/3x + 490

Step-by-step explanation:

2x +3y = 1470  

Slope intercept form definition: y = mx + b is the slope-intercept form of a line where m is the slope and b is the y-intercept.

2x + 3y = 1470

2x + 3y -2x = 1470 - 2x - Subtract 2x from both sides

3y = 1470 - 2x - Simplify

3y/3 = 1470/3 - 2x/3 - Divide both sides by 3

y = -2/3x + 490 - Simplify

-⅔ is the slope and 490 is the y-intercept

A Nashville-area radio station plays songs from a specific, fixed set of artists. The station has no DJ; instead, a computer randomly selects which songs to play. The songs themselves are picked randomly, and the same song may be played many times in a row. In the set of songs, 45% are sung by a female singer, 45% are sung by a male singer, and 10% are instrumental with no vocals. What is the probability that a particular set of 3 songs contains exactly 2 female singers and 1 male singer? (Hint: Be aware that there are multiple ways to achieve this pattern of songs.)

Answers

The answer is 27.3375%.

To calculate this, a multiplication rule is used. The multiplication rule calculates the probability that both of two events will occur. In this method, the possibilities of each event are multiplied.

So, we have three events occurring simultaneously:

1. set contains female singer: 45% = 0.45

2. set contains female singer: 45% = 0.45

3. set contains female singer: 45% = 0.45


Also, it should be taken into consideration that there are three set combinations:

female-female-male,

female-male-female,

male-female-female


So, the probability for one set of the song is:

0.45 × 0.45 × 0.45 = 0.091125

Therefore, the probability is multiple ways to achieve this pattern of songs):

3 × 0.091125 = 0.273375 = 27.3375%.

Answer:

B) 2187/8000

Step-by-step explanation:

do the math

trust

Simplify the following: a) ((w^-5)/(w^-9))^1/2
b) (m^6)^-2/3
c) (3x^-4y^5)/((2x^3y^-7))^-2

Answers

a. ((w^(-5))/(w^(-9) ))^{ (1)/(2) } \n  ( (w^(9) )/(w^(5) ))^{ (1)/(2) }   \n (w^(9-5))^{ (1)/(2) }   \n (w^(4))^{ (1)/(2) }  \n  \sqrt{w^(4) } \n w^(2)
b.(m^(6))^{ (-2)/(3) } \n  ((1)/(m^(6) ))^{(2)/(3) }  \n  \frac{ \sqrt[3]{1^(2) } }{ \sqrt[3]{m^(6) }^(2)  }  \n   \frac{ \sqrt[3]{1} }{m^(2*2) }   \n  (1)/(m^(4) )
Hope this helps!
Problem A
((w^(-5))/(w^(-9)))^{{(1)/(2)} = ((w^(9))/(w^(5)))^{{(1)/(2)} = (w^(4))^{{(1)/(2)} = \sqrt[2]{w^(4)} = w^(2)

Problem B

(m^(6))^{-(2)/(3)} = \frac{1}{(m^(6))^{(2)/(3)}} = \frac{1}{\sqrt[3]{(m^(6))^(2)}} = \frac{1}{\sqrt[3]{m^(12)}} = (1)/(m^(4))

Problem C
((3x^(-4)y^(5))/(2x^(3)y^(-7)))^(-2) = ((3y^(12))/(2x^(7)))^(-2) = ((3y^(12))^(-2))/((2x^(7))^(-2)) = ((2x^(7))^(2))/((3y^(12))^(2-)) = (4x^(14))/(9y^(24))